UPAYA PENINGKATAN HASIL BELAJAR IPS DENGANMENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STADPADA SISWA KELAS VA SDN 004 BAGAN BESAR DUMAI - Paidi ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is the process of learning social studies teacher-centered and teacher using the lecture method, so that students are less motivated in the learning process, so that students are less vigorously and actively ask in the delivery of learning materials. Efforts to fix the problem do action research, this study aims to improve the skills of teachers and student activities so as to improve learning outcomes IPS graders of SDN 004 VA Bagan Besar using cooperative learning model type STAD. The subjects were students of class VA SDN 004 Bagan Besar Dumai totaling 25 students consisting of male students and female students 11 students 14 students. The data used in this study are the activities of teachers and students and learning outcomes IPS. The results of this study indicate that although: (a) the activities of teachers obtain a score of 32 (61.54%) with enough categories, the first cycle II meeting given a score of 38 (73.01%) in both categories. In the second cycle meeting I obtained a score of 50 (96.15%) with a very good category, and the second cycle II meeting obtained a score of 51 (98.08%) with a very good category. Besides the student activity also increased, in the first cycle of meetings I obtain a score of 20 (62.5%) with enough categories, the first cycle II meeting obtain a score of 23 (68.75%) in both categories. In the second cycle meeting I obtained a score of 28 (87.5%) with a very good category, and the second cycle II meeting obtain a score of 30 (93.75%) with a very good category; and (b) the results of students in each cycle has increased, on the basis of the results of social studies scores students get low category with an average value of 48.8. In the first cycle obtain sufficient category with an average value of 56.92. And the second cycle obtain both categories with an average value of 73.84.